Tombland - Sansom, C. J (Sansom, C. J. Shardlake series., 2019)
When a distant relative of Princess Elizabeth is found dead, Matthew Shardlake is sent to investigate the murder, which may have connections reaching to a peasant rebellion sweeping the country.